Pengaruh Penggunaan Media Animasi Terhadap Kecerdasan Spiritual Anak - Icam Sutisna; Nurhayati Tine; Amalia Kartika Mohama (Student Journal of Early Childhood Education, 2023)
The aim of this study is to (1) understand the purpose of animated films, (2) understand the meaning of children's spiritual intelligence, and (3) determine the influence of animation media on children's spiritual intelligence. This research was conducted using a quantitative method and sampled early childhood children in group (B) at Bersehati State Kindergarten Binjeita, located in East Bolangintang District. The research method applied in this study was an experimental method with 8x applications of animation media treatment. The results of the study showed that the treatment of Nusa and Rara animated films had an influence on improving children's spiritual intelligence in Bersehati Kindergarten, Binjeita Village. The percentage increase was 38.46%. The hypothesis testing showed that the alternative hypothesis (H1) was accepted with a probability value of 0.000, where 0.000 < 0.05, indicating an influence of animation media usage on children's spiritual intelligence.